1998
DOI: 10.1177/004728759803700203
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Testing a Tourism Impact Scale

Abstract: A 35-item tourism impact scale was developed. It was de rived from an initial pool of 147 impact items drawn from personal interviews and the literature, and it was refined us ing classical scale-development procedures. The scale com prises seven domains: social and cultural, economic, crowd ing and congestion, environmental, services, taxes, and community attitudes, although the latter two domains did not always emerge as independent factors. Testing was under taken with three independent samples drawn from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
303
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(327 citation statements)
references
References 37 publications
10
303
0
14
Order By: Relevance
“…Compared with the response rate in other resident attitude studies, which have administered surveys by mail, the response rate of our surveys was low. For example, tourism development studies have reported response rates of 70% [8], 52% [27], 19% [71], and 14.6% [53]. The low response rate is one of the limitations of the research, which may minimize the generalizability of the findings.…”
Section: Data Collection and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the response rate in other resident attitude studies, which have administered surveys by mail, the response rate of our surveys was low. For example, tourism development studies have reported response rates of 70% [8], 52% [27], 19% [71], and 14.6% [53]. The low response rate is one of the limitations of the research, which may minimize the generalizability of the findings.…”
Section: Data Collection and Analysis Methodsmentioning
confidence: 99%
“…Community services satisfaction includes resident perceptions of the various government, business, and nonprofit services that are potentially influenced by tourism development [25]. Positive and negative tourism impacts consequently influence community conditions and services [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism impacts can be divided into three categories, namely, economic impact, social and cultural impact, and the impact of the environment [9] [10] .…”
Section: Tourism Impactmentioning
confidence: 99%
“…According to [9], the host communities seek to attract tourists to their area because of the industry's potential for improving existing economic and social conditions (i.e., the hosts' quality of life). Besides, "tourism generates jobs, wealth and revenues for government" [10, p.36].…”
Section: Literature Reviewmentioning
confidence: 99%